Predictive Value of Clinical and Pathological Characteristics for Metastatic Radioactive Iodine-Refractory Differentiated Thyroid Carcinoma: A 16-year Retrospective Study - Chai, Jinyan; Zhang, Ruiguo; Zheng, Wei; Zhang, Guizhi; Jia, Qiang; Tan, Jian; Meng, Zhaowei; Wang, Renfei (Frontiers in Endocrinology, 2022)
Purpose To assess predictive value of clinical and pathological characteristics for metastatic radioactive iodine-refractory differentiated thyroid carcinoma (RAIR-DTC) in early stage retrospectively. Methods We studied 199 metastatic DTC patients who were divided into two groups (TgAb negative and TgAb positive). The stimulated Tg (Sti-Tg) at the first and second radioiodine therapy (RIT) were defined as Sti-Tg1 and Sti-Tg2, the suppressed Tg (Sup-Tg) were designated as Sup-Tg1 and Sup-Tg2, while the TgAb were defined as TgAb1 and TgAb2, respectively. Univariate analysis and Logistic regression were used to investigate the effects of 13 observed factors to predict RAIR-DTC. Results In TgAb negative group, ROC curve analysis showed that cut-off values of age, Sti-Tg2/Sti-Tg1 and Sup-Tg2/Sup-Tg1 to predict RAIR-DTC were 40 years old, 57.0% and 81.0%, respectively. Age, extrathyroid invasion, Sti-Tg2/Sti-Tg1, Sup-Tg2/Sup-Tg1 and BRAF gene mutation were proved to be independent factors predicting RAIR-DTC. In TgAb-positive group, ROC curve analysis showed that cut-off values of age, TgAb1 and TgAb2/TgAb1 to predict RAIR-DTC were 55 years old, 297 IU/ml (14.8 times higher than the upper limit) and 53.6%, respectively. Conclusions For TgAb-negative DTC, age over 40, extraglandular invasion, mutated BRAF gene, Sti-Tg decreased less than 43%, and Sup-Tg decreased less than 19% after the first two courses of RIT were independent predictors for RAIR-DTC. For TgAb-positive DTC, age over 55, extraglandular invasion, mutated BRAF gene, distant metastasis before RIT, TgAb level 14.8 times higher than the upper limit, TgAb dropped less than 46.4% after two courses of RIT were influencing factors.